(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Phosphorus is an essential macronutrient for plant growth, yet its availability is often limited in acidic soils, posing challenges for crop productivity. Cowpea, a vital grain legume, responds positively to improved phosphorus levels under such conditions. Additionally, seed priming has emerged as an effective agronomic practice to enhance crop performance by activating key physiological processes. This study aimed to evaluate the combined effects of seed priming and phosphorus application on the growth and yield of cowpeas in field conditions at the Federal University Dutse during the spring of 2023. The experiment utilized a two-factorial randomized complete block design with three replications. Treatments included two seed priming methods (no priming and priming with 0.3% KNOâ‚ƒ for 24 hours) using the Osmo priming method and four phosphorus application rates (20, 30, 40, and 60 kg Pâ‚‚Oâ‚… haâ»Â¹). Significant differences (P < 0.05) were observed across various parameters. Primed seeds yielded the highest grain production (1.25 t haâ»Â¹), outperforming non-primed seeds (1.16 t haâ»Â¹). Phosphorus application significantly influenced yield attributes (P < 0.001), cowpea variety IT97K-499-35, popularly known (as Samba) was used, and, the highest grain yield (1.44 t haâ»Â¹) was achieved at 40 kg Pâ‚‚Oâ‚… haâ»Â¹. Interaction effects between seed priming and phosphorus application were also significant (P < 0.001). The combination of seed priming and 40 kg Pâ‚‚Oâ‚… haâ»Â¹ produced the highest grain yield (1.51 t haâ»Â¹). These findings suggest that using primed seeds in conjunction with 40 kg Pâ‚‚Oâ‚… haâ»Â¹ is a promising strategy for enhancing cowpea productivity.